2006
DOI: 10.1093/molehr/gal079
|View full text |Cite
|
Sign up to set email alerts
|

Hominoid-specific SPANXA/D genes demonstrate differential expression in individuals and protein localization to a distinct nuclear envelope domain during spermatid morphogenesis

Abstract: Human sperm protein associated with the nucleus on the X chromosome consists of a five-member gene family (SPANXA1, SPANXA2, SPANXB, SPANXC and SPANXD) clustered at Xq27.1. Evolved from an ancestral SPANX-N gene family (at Xq27 and Xp11) present in all primates as well as in rats and mice, the SPANXA/D family is present only in humans, bonobos, chimpanzees and gorillas. Among hominoid-specific genes, the SPANXA/D gene family is considered to be undergoing rapid positive selection in its coding region. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…SPANXA is an acidic protein and associates with other nuclear envelope proteins, but shows no significant similarity with known nuclear proteins or nucleic acid-binding proteins in the spermatid [16, 19]. These studies implied that SPANXA may interact with nucleic acids or other proteins in performing its functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPANXA is an acidic protein and associates with other nuclear envelope proteins, but shows no significant similarity with known nuclear proteins or nucleic acid-binding proteins in the spermatid [16, 19]. These studies implied that SPANXA may interact with nucleic acids or other proteins in performing its functions.…”
Section: Discussionmentioning
confidence: 99%
“…The SPANX (Sperm Protein Associated with the Nucleus on the X-chromosome) family encodes highly similar proteins that are exclusively expressed in normal testes as well as in certain tumors [14–17]. In adult human testes, SPANXA/D (A1, A2, B, C, and D) proteins are localized on the nuclear envelope of condensing non-acrosomal regions during spermiogenesis, and expressed in late spermatids and spermatozoa [18, 19]. SPANXA/D proteins have also been found in various tumors, such as melanoma, bladder carcinomas, myeloma, head and neck squamous cell carcinoma (HNSCC), as well as colorectal and prostate cancers [14, 20–23].…”
Section: Introductionmentioning
confidence: 99%
“…A recent case study provided the valuable insight into the biological role of testis-biased expressed new genes. A better-characterized case is SPANXA/D family, which consists of three X-linked sperm proteins associated with nucleus, SPANXA1, SPANXA2 and SPANXD present only in human and great ape [24]. It was found that during spermatid morphogenesis, the SPANXA/D protein migrated into the base of the sperm head [24].…”
Section: Primate- or Human-specific New Genes Are Often Implicated Inmentioning
confidence: 99%
“…The genes expressed during spermatogenesis comprise diploid and haploid expressed groups [1]. Many of the haploid, post-meiotically expressed genes have been mapped to autosomal chromosomes, but the s perm p rotein a ssociated with n ucleus in the X chromosome ( SPANX ) gene family is one of the few mapped to the X chromosome [2]–[4].…”
Section: Introductionmentioning
confidence: 99%